Septic Shock Induced by Bacterial Prostatitis with Morganella morganii subsp. morganii in a Posttransplantation Patient - Xiaofan Li; Jianhui Chen (Case Reports in Transplantation)
Bacterial infection is a common complication after Hematopoietic Stem Cell Transplantation (HSCT). Morganella morganii is ubiquitous Gram-negative facultative anaerobe, which may cause many kinds of opportunistic infection. Herein we report a case of a 55-year-old man who presented with frequent urination, urgency, and mild pain that comes and goes low in the abdomen and around the anus. The patient had a medical history of chronic prostatitis for 4 years. He received HLA-matched sibling allo-HSCT because of angioimmunoblastic T-cell lymphoma 29 months ago. The routine examination of prostatic fluid showed increased leukocytes and the culture of prostatic fluid showed Morganella morganii subsp. morganii. The patient developed chills and fever 18 hours after examination. Both urine culture and blood culture showed Morganella morganii subsp. morganii. The patient was successfully treated with antibiotic therapy and septic shock management. Taken together, Morganella morganii should be considered a possible pathogen when immunocompromised patients develop prostatitis. Also, prostatic massage could be a possible trigger of septic shock induced by Morganella morganii subsp. morganii in a posttransplantation patient.